The Making of Détente Soviet-American Relations in the Shadow of Vietnam - Nelson, Keith L. (Johns Hopkins University Press, 2019)
Originally published in 1995. In the early 1970s, largely as a result of the debilitating struggle in Vietnam, the United States began to reassess and redefine its basic approach to East-West relations. At the same time, the Soviet Union was awakening to the liabilities that a continuing and unregulated state of hostility would impose on its own internal and external agenda. Keith Nelson details the circumstances and traces the steps that led to the first significant accommodation and easing of tension between the superpowers during the Cold War. "In this important study, Keith Nelson explains the detente period in an imaginative, convincing, and impressively scholarly manner. Although there have been scores of books and memoirs on the subject, none have done the job quite like Nelson's. In particular, he has used post-glasnost Russian memoirs and monographs-and, especially, his own interviews with such key players as Dobrynin and Arbatov-to present one of the most intelligent Kremlinological studies I have ever seen." -Melvin Small, Wayne State University